1989
DOI: 10.1002/1097-4679(198909)45:5<718::aid-jclp2270450506>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity and teratogenicity vs. psychogenicity: Psychological characteristics associated with self-reported agent orange exposure among Vietnam combat veterans who seek treatment for substance abuse

Abstract: This study asked, “What are the psychological characteristics of Vietnam combat veterans who claim Agent Orange exposure when compared with combat‐experienced cohorts who do not report such contamination?” The question was researched among 153 heroin addicts, polydrug abusers, and chronic alcoholics who were seeking treatment: 58 reported moderate to high defoliant exposure while in combat; 95 reported minimal to no exposure while in Vietnam. The null hypothesis was accepted for measures of childhood and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Self-reported herbicide exposure also is associated with PTSD, anxiety, and depression. This seems puzzling, but one recent investigation found reports of herbicide exposure related to subjective distress among veterans (Robinowitz et al, 1989). In addition, it has been reported that perceived herbicide exposure is positively associated with a battery of self-reported negative health outcomes (Decoufle, Holmgreen, Boyle, & Stroup, 1992).…”
Section: Predictors Of Current Mental Health Statusmentioning
confidence: 99%
“…Self-reported herbicide exposure also is associated with PTSD, anxiety, and depression. This seems puzzling, but one recent investigation found reports of herbicide exposure related to subjective distress among veterans (Robinowitz et al, 1989). In addition, it has been reported that perceived herbicide exposure is positively associated with a battery of self-reported negative health outcomes (Decoufle, Holmgreen, Boyle, & Stroup, 1992).…”
Section: Predictors Of Current Mental Health Statusmentioning
confidence: 99%
“…45 The increased rates of psychiatric comorbidities in this subset of veterans may suggest a potential psychogenic component to some of the health issues encountered after their Vietnam service, and in the case of perceived Agent Orange exposure, self-reporting and apprehension about the long-term effects may be a vehicle for the expression of psychological distress in some instances. 46 When evaluating the CDC Vietnam experience study, veterans selfreported an increased incidence of parasitic infections, benign neoplasms, dyschromia, unspecified skin symptoms, rash not otherwise specified, psoriasis, hypertrichosis, and urticaria. However, the same study found only a statistically significant increased prevalence of tinea versicolor, milia, and epidermoid cysts when the same veterans were examined by board-certified dermatologists.…”
Section: Limitations To Studying Vietnam Exposuresmentioning
confidence: 99%